2018
DOI: 10.1016/j.aninu.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Fecal scores and microbial metabolites in weaned piglets fed different protein sources and levels

Abstract: This experiment studied the effects of dietary protein sources and levels on the gut health of piglets, pH value, and concentrations of microbial metabolites (ammonia-N, volatile fatty acids [VFA], and polyamines) in the distal colonic and proximal colonic digesta of piglets weaned at 21 d of age. A total of 150 early-weaned piglets were allotted randomly to 5 diets: 1) control diet (CT; 17% CP), 2) CT formulated with more soy protein concentrate (SPC19; 19% CP), 3) more fish meal (FM19; 19% CP), 4) CT formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 28 publications
3
28
1
Order By: Relevance
“…Table 3 presented the effect of feeding extruded linseed: walnut meal mixture (8:1) on fecal scores (FS) and incidence of diarrhea (ID) in weaned piglets. Fecal score reflects the digestive health of piglets, a high score indicates high incidence of diarrhea (Wen et al, 2018). In our study, fecal score was decreased by 10.71% at day 7 PW (P>0.05), and at day 21 PW it was observed a decreasing tendency by 17.05% FS as a response to dietary mixture addition (P=0.07).…”
Section: Intestinal Healthsupporting
confidence: 47%
“…Table 3 presented the effect of feeding extruded linseed: walnut meal mixture (8:1) on fecal scores (FS) and incidence of diarrhea (ID) in weaned piglets. Fecal score reflects the digestive health of piglets, a high score indicates high incidence of diarrhea (Wen et al, 2018). In our study, fecal score was decreased by 10.71% at day 7 PW (P>0.05), and at day 21 PW it was observed a decreasing tendency by 17.05% FS as a response to dietary mixture addition (P=0.07).…”
Section: Intestinal Healthsupporting
confidence: 47%
“…Stress associated with weaning is often accompanied by increased susceptibility to metabolic disorders, and impaired structure and function of the small intestine (Campbell, Crenshaw, & Polo, 2013; Wen et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The first 14 days after weaning are often followed by increased activation of the immune system, which contributes to the anatomical and functional breakdown of the intestinal epithelium (Hu, Xiao, Luan, & Song, 2013; Wen et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pig, feed intake is related to energy concentration of the diet and high energy level in the diet decrease feed intake where as low energy intake decreases protein deposition (Lewis and Southern, 2001;Noblet and Van Milgen, 2013). It was reported that the pig feed containing low protein improved faecal consistency score, enteric health and growth performance (Opapeju et al, 2015;Wu et al, 2015;Wen et al, 2018). Th erefore, present study was conducted to observe the effect of different levels of protein and energy which were either equal to or below the requirement of Bureau of Indian Standard (BIS, 1986) on growth and nutrient utilization in crossbred grower pig.…”
Section: Introductionmentioning
confidence: 93%